Structural evolution in reactive RF magnetron sputtered (Cr, Zr)2O3 coatings during annealing. (1st June 2017) - Landälv, L.; Lu, J.; Spitz, S.; Leiste, H.; Ulrich, S.; Johansson-Jõesaar, M.P.; Ahlgren, M.; Göthelid, E.; Alling, B.; Hultman, L.; Stüber, M.; Eklund, P.
Abstract: Reactive RF-magnetron sputtering is used to grow Cr0.28 Zr0.10 O0.61 coatings at 500 °C. Coatings are annealed at 750 °C, 810 °C, and 870 °C. The microstructure evolution of the pseudobinary oxide compound is characterized through high resolution state of the art HRSTEM and HREDX-maps, revealing the segregation of Cr and Zr on the nm scale. The as-deposited coating comprises α-(Cr, Zr)2 O3 solid solution with a Zr-rich (Zr, Cr)Ox amorphous phase. After annealing to 750 °C tetragonal ZrO2 nucleates and grows from the amorphous phase. The ZrO2 phase is stabilized in its tetragonal structure at these fairly low annealing temperatures, possibly due to the small grain size (below ∼30 nm). Correlated with the nucleation and growth of the tetragonal-ZrO2 phase is an increase in hardness, with a maximum hardness after annealing to 750 °C, followed by a decrease in hardness upon coarsening, bcc metallic Cr phase formation and loss of oxygen during annealing to 870 °C. The observed phase segregation opens up future design routes for pseudobinary oxides with tunable microstructural and mechanical properties. Graphical abstract: Image